2022 IEEE International Conference on Big Data (Big Data) 2022
DOI: 10.1109/bigdata55660.2022.10021025
|View full text |Cite
|
Sign up to set email alerts
|

Handwritten Word Recognition using Deep Learning Approach: A Novel Way of Generating Handwritten Words

Abstract: A handwritten word recognition system comes with issues such as-lack of large and diverse datasets. It is necessary to resolve such issues since millions of official documents can be digitized by training deep learning models using a large and diverse dataset. Due to the lack of data availability, the trained model does not give the expected result. Thus, it has a high chance of showing poor results. This paper proposes a novel way of generating diverse handwritten word images using handwritten characters. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 45 publications
0
5
0
Order By: Relevance
“…Also, the authors in [27] a method for generating diverse handwritten word images using handwritten characters is proposed. The approach involves training a BiLSTM-CTC architecture with synthetic handwritten words generated in two ways: overlapped and non-overlapped.…”
Section: Results Discussionmentioning
confidence: 99%
“…Also, the authors in [27] a method for generating diverse handwritten word images using handwritten characters is proposed. The approach involves training a BiLSTM-CTC architecture with synthetic handwritten words generated in two ways: overlapped and non-overlapped.…”
Section: Results Discussionmentioning
confidence: 99%
“…A graphical comparison with earlier research is shown in Fig. 10, and a comparison of the suggested method's performance metrics with those of Alonso et al [3], Gan et al [4], Luo et al [5], Fogel et al [6], Akter et al [9] and Kang et al [14] is shown in Table 4.…”
Section: Evaluation Of the Approach Against Prior Workmentioning
confidence: 87%
“…Wang et al [8] highlighted the benefits of transfer learning in speech and language processing. In order to improve handwritten word recognition using synthetic datasets, Akter et al provided a deep-text-recognition-benchmark (BiLSTM-CTC) based technique that shows promise in tackling data scarcity, especially for languages like Bangla [9]. A fresh assessment metric was introduced by Tüselmann et al [10] to solve problems in semantic word recognition.…”
Section: Literature Surveymentioning
confidence: 99%
“…The number of hate samples in each category is imbalanced. Akter et al (2022) [10] have classi ed aggressive comments in Hindi, Bangla, and English datasets using LSTM, BiLSTM, LSTMAutoencoder, word2vec, BERT, and GPT-2 models and have also shown a novel way of generating machine-translated data to resolve data unavailability issues. The BERT model performed best on noisy datasets, with 78% accuracy, while the GPT2 model performed best on raw datasets that did not contain any noise, with 80% accuracy.…”
Section: Related Workmentioning
confidence: 99%